Computer mediated parent-teacher communication = La comunicación entre padre-maestro mediada por computadora - Juniu, Susana
Parent-teacher communication is crucial to children's education. The literature reveals that parents' involvement in their children's education improves outcomes in areas such as learning, attendance, behavior, and graduation rates. Increased and meaningful communication between home and school is likely to enhance parent involvement and may consequently support students' learning. Schools are using various forms of technology to increaseschool/home communication, including voice mail, e-mail, school and classroom websites, and web access to individual student information such as attendance, grades, and student portfolios; however, this use is not consistent or widespread. This paper examines the most prevalent parent-teacher communication in a K-12 educational setting and explores various communication options to improve parent-teacher communication. The focus is to examine the communication needs between teacher and parents and the benefits of combining traditional synchronous and asynchronous communication with newer communication technologies to meet these needs.